Self-help skills improve independence of activities daily living in pre-school children with child abuse - Lusty, Junita; Sutini, Titin; Purwati, Nyimas Heny; Srisantyorini, Triana (Riset Informasi Kesehatan, 2025)
Background: Children who are abused are prone to delayed growth and development, including the development of independent Activities Daily Living (ADL). Self-help skills are motor skills that can help children to fulfill basic needs independently through Activities Daily Living (ADL). Therefore, adults around them, including caregivers in orphanages, need to teach self-help skills to improve children's ADL independence. Objectives: This study aims to determine the effect of self-help skills on Activities Daily Living (bathing, brushing teeth, personal hygiene, toileting, dressing, and eating) independence in pre-school children with child abuse which is measured by ADLIC (Activities of Daily Living Iranian Children). Methods: Respondents in this study were pre-school children with child abuse who were given self-help skills with a total of 36 respondents divided into intervention and control groups. The research design used a quasi-experimental design with a non-equivalent control group pre-post test. The bivariate analysis used in bathing, brushing teeth, personal hygiene, and toileting variables was paired t-test, while the variables of dressing and eating was used Wilcoxon Signed Rank Test. Results: The p-value result in the intervention group is 0.000 (<0.05) which indicates that there is a difference in ADL ability from before and after the intervention. In the control group, the p-value> 0.05 was obtained, indicating that there was no difference between ADL abilities before and after. There is a significant average increase in the intervention group compared to the control group. Conclusion: The results of this study indicate that there are average increase in the independence of Activities Daily Living (ADL) in pre-school children with child abuse in the intervention group after being given treatment in the form of self-help skills. Therefore, it is hoped that all parties involved in the care of children with a history of child abuse are able to minimize the impact that occurs due to child abuse and understand the concept of self-help skills that support the development of the independence of ADL.